The coating with ZrO2-coated hollow glass microspheres: Low solar absorption and high microwave transmittance - Yu Yang; Miao Jiang; Zhuang Ma; Alexandr A. Rogachev; Weizhi Tian; Xin Gao; Baowen Xu; Lihong Gao (Materials & Design, 2023)
Carbon fiber epoxy resin (CFRP) is gradually used as the space satellite antenna material, thermal control coatings (TCCs) are prepared on the surface to ensure the stable operation. However, the traditional TCCs have no wave transmission capability. The hollow glass microspheres (HGMs) were used to prepare the coating in our work, and ZrO2 was coated on its surface (Zr-HGM) to improve the solar reflectivity. The Zr-HGM powders were obtained by a homogeneous precipitation method with an appropriate reaction time of 4 h. By investigating the optical and dielectric properties, we found that the solar absorption of the coating with Zr-HGM was reduced by half compared to the coating with the original HGM. The microwave transmittances were all above 96.5% from 2 to 18 GHz. Our findings have proposed a preparation method for a new CFRP-based TCC, which will ensure the stable operation of the satellite antenna.